Building materials: earth fights back - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Sun-dried mixtures of clay and sand are still widely used in tropical buildings. Despite strong competition from other buildingmaterials such as concrete and cement blocks, which have benefited from the image of being modern and 'European',...